Profil Kompetensi Profesional Guru Mapel Biologi Pasca Sertifikasi di Karesidenan Surakarta - Anif, Sofyan (Jurnal Varidika: Varia Pendidikan, 2013)
As stated in UU No. 14, 2005 and PP No. 74, 2008 that teachers as proffessional educator have to possess four competences, namely: pedagogic, proffessional, character, and social. However the condition in Indonesia is not like that. In general, they are in low category, specifically in pedagogic and proffessional. Those conditions happen in biology teachers and other teacher subjects. Then the aim of this study is to observe the profile of biology teachers especially their proffessional competence pasca sertification in Surakarta residance. The population of this study is all biology teachers (332 persons) that have rechieved sertification through direct, portofolio, and PLPG program. Purposive random sampling is used to get 116 teachers. Data are collected by depth interview, documentation, and test, then the collected data are analysed by descriptive qualitative. The result shows that the profile of proffessional competence of biology teachers can be grouped into three: low, middle, and high. The teachers are low in: concept implementation, using tool of measurements, biology experiment planning, using the result of reflection, self reflection, understanding the principles and theories of savety work, doing action research, and understanding the steps of biology experiement correctly. The teachers are middle in: understanding the objective of the study, creative and innovative in implementing and developing science of biology nad correlated sciences, undesrtanding thinking process of biology, using symbolic language, undesrtanding standard competence, and understanding the scoupe of biology. They are high in: understanding the structure biology science and its correlation, selecting the material, cooking the material creatively, understanding the concepts, laws, and biology theories, undesrtanding the history of the natural science, specifically biology, understanding the basic competence of the subject or topic, updating their knowledge from many sources, and rationally qualitatively and quantitatively in understanding the process and biology law.